Common mental disorders and risk of female infertility: a two-sample Mendelian randomization study - Mao, Di; Lin, Mingmei; Li, Rong (Frontiers in Endocrinology, 2024)
Introduction Female infertility is a global issue that impacts on public health seriously and many mental disorders are observed in infertility groups. Methods To investigate the casual relationship between those, genome-wide association studies summary data of anxiety disorder (n=9,897), broad depression (n=322,580), major depressive disorder (n=480,359 and n=500,199), bipolar disorder (n=51,710), insomnia (n= 462,341), and female infertility (n=126,342) were extracted from the existing datasets and was analyzed through the two-sample mendelian randomization study. The following heterogeneity and sensitivity test were applied to ensure the robustness of results. Results Based on inverse variance weighted results, major depressive disorder was associated with female infertility (P = 0.0001, odds ratio 1.396, 95 % confidence interval 1.175–1.658). No causal relationship was identified between the other four mental disorders and infertility. was found. Additionally, reverse mendelian randomization did not indicate a causal relationship among these disorders. Discussion The early identification and management of anxiety symptoms in women of reproductive age, in conjunction with the effective treatment of major depressive disorder, may be crucial for preserving female fertility.